Influence of high mobility group box 1 (HMGB1) derived from SCC7 cells on mouse normal tongue muscle fibers. Issue 5 (September 2018) - Takizawa, Shota; Sakiyama, Koji; Bando, Yasuhiko; Inoue, Katsuyuki; Sakashita, Hide; Ogasawara, Yudai; Amano, Osamu; Sakashita, Hideaki
Abstract: Objective: High mobility group box 1 (HMGB1) is present in the nucleus of all normal cells and known for its participation in the maintenance of homeostasis. But recent studies suggested an association with the invasion and metastasis of cancer. Therefore, we aimed to clarify how HMGB1 released from cancer cells affects mice tongue muscle fibers. Methods: In this study, we conducted immunohistochemical investigation of the localization of HMGB1 and the receptor for advanced glycation endproducts (RAGE) in the carcinoma and adjacent muscle tissues of the consecutive serial frontal section of mice tongues, into which SCC7 cells (isolated from a murine squamous cell carcinoma) had been implanted. The amounts of HMGB1 and RAGE mRNAs expressed were also examined. Results: At first, observation of hematoxylin/eosin-stained sections showed muscle fibers that had become reduced in size in the anterior and middle tongue from the SCC7 group. Immunohistochemical staining revealed that HMGB1 and RAGE were expressed not only in the carcinoma but also in the muscle fibers peripheral of the carcinoma and distal to the carcinoma. As with the immunohistochemical staining, mRNA expression levels of HMGB1 and RAGE were also expressed in the carcinoma and peripheral/distal muscle fibers. Conclusion: These results indicated the HMGB1 protein released from the carcinoma had reduced the size of the muscle fibers, through the RAGE. Furthermore, the possibility that this promotes cancer invasion through the formation of a clearance gap in high density skeletal muscle tissue was suggested.